2015
DOI: 10.3923/ajpsaj.2015.165.171
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Quality of Fresh and Smoked Guinea Fowl Meat Sold in the Bolgatanga Municipality, Ghana

Abstract: The study was conducted to determine the microbial quality of fresh (raw or uncooked) and smoked guinea fowl meats sold in the Bolgatanga Municipality of Ghana. Observations were also made to know the hygienic conditions under which guinea fowls are slaughtered and smoked. Guinea fowl meat samples were obtained from five different retail shops in the Bolgatanga Municipality. Twenty meat samples each (10 fresh and 10 smoked guinea fowl meats) were collected from five different retail shops. Collected samples we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 18 publications
2
24
0
Order By: Relevance
“…Res. Bacteriol., 8 (2): 34-40, 2015 Besides water samples, Escherichia coli have been isolated from farm animals, wild animals, pests, humans, vegetables and many more (Shakak and Saeed, 2010;Abulreesh, 2011;Adzitey et al, 2011Adzitey et al, , 2012aAdzitey et al, , 2013Adzitey et al, , 2014Adzitey et al, , 2015bManikandan et al, 2011;Geidam et al, 2012;Kumar et al, 2013;Al-Sultan et al, 2014;Biswas et al, 2014). Escherichia coli have been responsible for a number of foodborne outbreaks, diseases and deaths in some cases (CDC., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Res. Bacteriol., 8 (2): 34-40, 2015 Besides water samples, Escherichia coli have been isolated from farm animals, wild animals, pests, humans, vegetables and many more (Shakak and Saeed, 2010;Abulreesh, 2011;Adzitey et al, 2011Adzitey et al, , 2012aAdzitey et al, , 2013Adzitey et al, , 2014Adzitey et al, , 2015bManikandan et al, 2011;Geidam et al, 2012;Kumar et al, 2013;Al-Sultan et al, 2014;Biswas et al, 2014). Escherichia coli have been responsible for a number of foodborne outbreaks, diseases and deaths in some cases (CDC., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of Escherichia coli and Salmonella enterica in the gastrointestinal tract of guinea fowls present opportunity for cross contamination unto carcasses during processing. Adzitey et al (2015) found Escherichia coli and Salmonella enterica in fresh and smoked guinea fowls and attributed them to poor processing during dressing and cross contamination from their natural habitat. Kilonzo-Nthenge et al (2018) isolated Salmonella enterica from 23% of whole carcass rinses of guinea fowl.…”
Section: Discussionmentioning
confidence: 99%
“…Guinea fowls (Numida meleagris) in Ghana are dominated by local or traditional breeds reared mostly in Northern part of Ghana. The meat of guinea fowls is cherished and relished by many Ghanaians (Adzitey et al, 2015). Nonetheless, they are kept mainly under the extensive and semi-extensive systems, and are exposed to a variety of bacteria during scavenging (Teye et al, 2000;Adzitey et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result agreed with Bojesen et al (2011), who noted that 97%of field strains were resistant to tetracycline, also agreed with Dewhirst et al, (1993); Janda (2011) and Jones et al, (2013).Other result optained by Bojesen et al(2007) who recorded that all isolates were sensitive to amoxicillin-calivulinic acid and El Bestawy 2014 who recorded that they resistant to sulpha. Trimethoprim.The differences in resistance patterns are widely due to factors which include differences in geographical locations, particular bacteria species involved, the animal production systems, the extent to which antibiotics are used, sampling techniques and period of sampling (Adzitey et al,2015).…”
Section: Molecular Characterization Of Virulence Genes Of Ganatis:-mentioning
confidence: 99%